2010
DOI: 10.1111/j.1365-2222.2010.03558.x
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost has potent anti‐inflammatory properties on human monocyte‐derived dendritic cells

Abstract: In summary, our results provide evidence that iloprost profoundly affects the function of human myeloid DCs. Therefore, iloprost might also be a new therapeutical option for the treatment of asthma in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Iloprost binds to several prostanoid receptors, with IP mediating most of its effects 29 32. When we blocked IP by CAY10449 antagonist the effects of iloprost were almost completely abolished, while no effects were observed when EP4 was blocked by AH23848 in both SSc and HD (figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iloprost binds to several prostanoid receptors, with IP mediating most of its effects 29 32. When we blocked IP by CAY10449 antagonist the effects of iloprost were almost completely abolished, while no effects were observed when EP4 was blocked by AH23848 in both SSc and HD (figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…PGI 2 analogues downregulate lymphocyte adhesion to endothelial cells24 and inhibit the production of tumour necrosis factor α (TNFα) by human lymphocytes,25 26 monocytes27 28 and dendritic cells 20 29 30. Iloprost consistently decreases TNFα levels in BAL fluid of bleomycin-treated mice 31.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PGI 2 is regarded as a potential treatment of asthma by their antiinflammatory effect in vitro (14,30) and in animal model (15). The antiinflammatory effect of PGI 2 analogs by altering the function of DCs has been revealed by our previous work using human plasmacytoid DCs (16) and by the work of Muller et al (31) using human monocyte-derived DCs (31). However, the effect of PGI 2 analogs on human mDCs is not elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…40 In human studies, PGI 2 analogs have been shown to suppress TNF-α expression in human primary monocytes 41 and in plasmacytoid DCs. 11 Very recently, Muller et al 42 reported that iloprost inhibits inflammatory cytokine production by human MDDCs and induces the generation of regulatory T cells. The present study additionally demonstrated the role of PGI 2 analogs in regulating the expression of costimulatory molecules for the maturation of human MDDCs, supporting the current evidence for the candidacy of the PGI 2 analog as a modulatory agent in treating asthma.…”
Section: Discussionmentioning
confidence: 99%